Ruling on tourism of infidels in Islamic countries - Muhammad Sami Farhan, (Islamic Sciences Journal, 2024)
ABSTRACT International tourism has spread widely in recent times and has begun to generate significant financial income for Muslim countries. The budgets of some Islamic countries have become based on tourism and cannot be dispensed with, due to its great economic benefits in addition to its benefits in other areas. Tourism, whose purpose is to move from one place to another for the purpose of contemplation and contemplation. There is nothing wrong with God’s creation, getting to know peoples and tribes, seeking praiseworthy knowledge, calling to Islam, jihad in its path, recreation, and performing religious obligations and duties, there is nothing wrong with it provided that all of that is governed by the provisions and rules of Islamic law so that it is valid and beneficial, and the jurists - may God have mercy on them - were God - they traveled from one place to another in search of knowledge, and the preachers were roaming the globe to spread the call of Islam, and the Mujahideen were leaving their families, homes and money for the sake of the call so that the word of Allah would be supreme, and Muslim merchants were moving from one country to another for trade and for the call, and these are all examples of forms of Tourism praised in Islam.